2003
DOI: 10.1017/s0266464x02000076
|View full text |Cite
|
Sign up to set email alerts
|

Archive or Memory? The Detritus of Live Performance

Abstract: The positive valuation of theatre as live performance, and therefore also its transience, is frequently accompanied by the urgent expression of the need to counter that transience by means of documentation. This desire to ‘save’ theatre reaches its most fervent expression (and hope of authority and permanence) with the live performance archive. Archive theory, however, now insists on the instability and uncertainty of the archive, which not only documents but also constructs its subject. In this article, Matth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 8 publications
(12 reference statements)
0
10
0
1
Order By: Relevance
“…24.For a detailed critique of the implicit and explicit ways that archives have been assumed to be a “true record of the past” see Reason (2003, especially pp. 83–85).…”
Section: Notesmentioning
confidence: 99%
“…24.For a detailed critique of the implicit and explicit ways that archives have been assumed to be a “true record of the past” see Reason (2003, especially pp. 83–85).…”
Section: Notesmentioning
confidence: 99%
“…(Phelan 1993, p. 149) In contrast, Philip Auslander suggested that performance and mediatization are more entangled, since 'the very concept of live performance presupposes that of reproduction' (Auslander 1997, p. 55). Matthew Reason has gone further, understanding the archive not as representation or mimesis, but as 'detritus': the 'fragments and echoes of the performance' (Reason 2003(Reason , 2006. In this view, far from being an authoritative archive of the past, the archive is partial.…”
Section: IVmentioning
confidence: 99%
“…This is the attraction of the archive for the performing arts researcher: as each performance disappears the archives offers the possibility of supplementing and perhaps supplanting doubtful memory as the site of performance record." 14 And yet, despite the research and documentation challenges posed by the ephemerality of performance, an alternative perspective of archives emphasizes the performance act from the fixed record. Diana Taylor distinguished the "archive of supposedly enduring materials" and the mythical notions of unmediated archival authority, from "the so-called ephemeral repertoire of embodied practice/knowledge (i.e., spoken language, dance, sports, ritual)."…”
Section: A Theatrical View Of Archivesmentioning
confidence: 99%